Acquired Motility Disorders in Childhood - PJ Milla (Canadian Journal of Gastroenterology)
Acquired motility disorders in childhood cause a number of gastrointestinal symptoms – principally, recurrent vomiting, abdominal pain and distension, constipation and loose stools. Gastrointestinal motility disorders result from disturbances of the control mechanisms of gut motor activity, which may be produced by organic disease involving enteric nerves and muscle, perturbation of the humoral environment of the nerves and muscle, and altered central nervous system input. In children, both congenital and acquired disease processes may produce these pathogenetic mechanisms, resulting in syndromes that vary in severity from chronic intestinal pseudo-obstruction to the irritable bowel syndrome.